Medical-grade modified PEEK composite material and preparation method thereof
By adding bioactive materials to polyether ether ketone materials and using diphenylsulfone solvent for polymerization and cooling treatment, a composite powder with microsphere structure is formed, which solves the poor binding ability of polyether ether ketone materials in human body and traditional powders. The problem of low efficiency of the crushing process achieves high biological activity and mechanical properties of the material and meets medical implantation standards.
Patent Information
- Application Number
- CN202411565476.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-18
AI Technical Summary
Polyether ether ketone materials have poor binding ability to cells after implantation into the human body, resulting in poor integration ability with bones. The traditional powder crushing process consumes a large energy and low production efficiency, which affects the mechanical properties and biological activity of the material.
By adding bioactive materials to the polyether ether ketone matrix and using diphenyl sulfone as solvent to dissolve the polyether ether ketone, polymerization reaction and cooling treatment are carried out to form a composite powder with microsphere structure, reducing nanoparticle agglomeration and improving the material Bioactivity and mechanical properties.
The bioactive materials are uniformly dispersed in the PEEK matrix, the composite materials have stable and uniform performance, and meet the medical implant grade polyether ether ketone material standards, reducing production costs and energy consumption.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to a medical-grade modified PEEK composite material and a preparation method thereof, and belongs to the field of polymer materials. Background Art
[0002] Polyetheretherketone (PEEK) is a polymer material with good biocompatibility, chemical stability and outstanding mechanical properties. It is also X-ray transparent and can maintain its original properties under long-term exposure to high-temperature steam, gamma rays and ethylene oxide. In recent years, medical-grade PEEK materials have been widely used in clinical medicine. In addition, PEEK is non-biotoxic, corrosion-resistant, lightweight and high-strength. Its elastic modulus (3-4 GPa) is close to that of human bones (14 GPa for compact bone and 1 GPa for trabecular bone). Compared with titanium alloys with higher elastic modulus (106-155 GPa), PEEK implants can reduce the occurrence of postoperative "stress shielding". Therefore, PEEK can be used to replace metal to manufacture human bones. Compared with industrial-grade PEEK, medical-grade PEEK requires subsequent refining and purification processes to meet the standards of medical implant-grade PEEK materials for human implantation.
[0003] However, polyetheretherketone is biologically inert, which makes it have poor ability to bind to cells after being implanted in the human body. When the bioinert material exists in the body for a long time, it reacts with the biological body in an exudative tissue reaction (mainly fibrinogen exudation), forming fibrous capsules on its surface, resulting in poor integration with bone, and it is difficult to form a stable interface and fuse with it. Therefore, it is necessary to add some bioactive materials to the polyetheretherketone material to improve the bioactivity of the composite material and broaden its application in the medical field of human implantation. At present, the method of mixing PEEK and bioactive nanomaterials is through ball milling, high-speed stirring or twin-screw extrusion. However, since PEEK has a large viscosity and is insoluble in solvents at room temperature, and nanoparticles have a relatively large specific surface area, agglomeration is easy to occur in the PEEK matrix, which greatly affects the mechanical properties of PEEK composite materials.
[0004] At present, the method of preparing polyetheretherketone fine powder mostly adopts low-temperature mechanical crushing technology, and low-temperature crushing technology uses liquid nitrogen freezing, which can make polyetheretherketone materials reach higher brittleness at low temperature, making it easier to perform mechanical crushing. However, the entire production process consumes a lot of energy, resulting in an increase in production costs. At the same time, the production efficiency of ultrafine powder prepared by low-temperature mechanical crushing technology is low, the material needs to be crushed multiple times to achieve a relatively ideal particle size requirement, and the powder morphology obtained is very irregular. The dissolution sedimentation method is to dissolve the material to be prepared into powder in a specific solvent, and then use cooling, evaporation and other methods to precipitate it in the solution system. By controlling the precipitation conditions, such as temperature, time, etc., the particle size and morphology of the powder are regulated, and finally a powder with uniform particle size distribution and regular powder morphology is obtained. Related reports use concentrated sulfuric acid as a solvent to prepare PEEK powder material by dissolution sedimentation method. However, when PEEK is dissolved in concentrated sulfuric acid solvent, the molecular chain structure of PEEK will be changed and it will be sulfonated to form SPEEK. Compared with PEEK, the solvent resistance, heat resistance and mechanical properties of sulfonated SPEEK are reduced. Summary of the invention
[0005] The purpose of the present invention is to provide a bioactive material / polyetheretherketone composite material, which meets the standards of medical implant-grade polyetheretherketone materials, and the bioactive material is evenly dispersed in the PEEK matrix, and the performance of the composite material is stable and uniform.
[0006] Different from the traditional powder crushing process, the present invention controls the process and obtains spherical composite powder with a particle size within a certain controllable range through simple crushing. The polyetheretherketone ultrafine powder with a lower particle size obtained after crushing is beneficial to the purification of polyetheretherketone, so as to improve production efficiency and reduce costs.
[0007] The method for preparing the medical-grade bioactive material / PEEK composite powder provided by the present invention comprises the following steps: S1, dispersing the bioactive material in the dissolved diphenyl sulfone, and heating until the solvent evaporates to obtain a bioactive material / diphenyl sulfone composite material; S2, adding the bioactive material / diphenyl sulfone composite material into a reaction kettle, heating under an inert atmosphere until the diphenyl sulfone is melted, adding sodium carbonate, difluorobenzophenone and hydroquinone, and continuing heating to react; S3, heating the polymer product of step S2, and then cooling it to 250-260°C; when the temperature drops to 250°C, cooling it naturally, and crushing the obtained sample with a crusher, and washing it with acetone and water or ethanol and water respectively.
[0008] In the preparation method of the present invention, in step S1, the bioactive material may be a medical filler; The medical filler can be nano-TiO2, nano-SiO2, hydroxyapatite nanoparticles, nano-calcium phosphate and graphene oxide; The amount of the bioactive material added is not higher than 35% of the mass of the PEEK resin.
[0009] In the preparation method of the present invention, in step S1, acetone, ethanol or ether is used to dissolve the diphenyl sulfone; After dispersing the diphenyl sulfone, ultrasonic treatment is performed, and the mixture is heated to 60-80° C. until the solvent is completely volatilized, and the mixture is performed under mechanical stirring.
[0010] In the preparation method of the present invention, in step S2, the temperature is raised to 150-180° C. to melt the diphenyl sulfone.
[0011] In the preparation method of the present invention, in step S2, heating is continued to rise to 300-320° C. for reaction for 2-3 hours.
[0012] Step S2 is performed under an inert atmosphere to prevent the bioactive material from undergoing an oxidation reaction.
[0013] In the preparation method of the present invention, in step S3, the diphenyl sulfone is heated to 290-300° C., the polymerization product is added, and then the temperature is lowered.
[0014] In the preparation method of the present invention, in step S3, the cooling rate is 5-20 °C / min; After cooling to 250-260°C, spherical particles are precipitated, which are microsphere structures. After cooling and simple crushing, fine powder of composite materials can be obtained. The obtained fine powder has a small particle size, which is more conducive to the refining and purification of organic solvents such as acetone or ethanol and pure water. After simple and efficient washing, fine powder of medical-grade bioactive material / PEEK composite material is obtained, which meets the standards of medical implant-grade polyetheretherketone materials for human implantation and improves the biological activity of PEEK materials.
[0015] In the preparation method of the present invention, in step S3, after washing, suction filtration and vacuum drying are performed, and the vacuum drying temperature is 100-150° C. and the time is 4-8 h.
[0016] The medical-grade bioactive material / PEEK composite powder prepared by the method of the present invention also falls within the protection scope of the present invention.
[0017] The present invention has the following beneficial technical effects: 1. Usually, the bioactive material / PEEK composite material is prepared by physically blending the two or dispersing them in a specific solvent. However, the present invention first prepares the bioactive material / diphenyl sulfone composite material. During the PEEK polymerization reaction, the added nanoparticles serve as effective nucleation sites. The PEEK polymer grows with the nanoparticles as crystal nuclei, so that there is steric resistance potential energy between the particles, thereby increasing the potential barrier between the particles and effectively reducing the agglomeration of the nanoparticles.
[0018] 2. When diphenyl sulfone is used as a solvent to dissolve polyetheretherketone, the chemical structure of the obtained powder will not be destroyed, and there will be no sulfonation phenomenon when dissolved in concentrated sulfuric acid, which greatly retains the mechanical properties and thermal stability of polyetheretherketone.
[0019] 3. By controlling the concentration of polyetheretherketone in the system and adjusting the cooling temperature, the particles of polyetheretherketone are made into a microspherical structure; low-particle-size ultrafine powder can be obtained by traditional mechanical crushing, and the particle size of the powder can be adjusted within the range of 10-50 μm; the particle size of the fine powder after crushing is smaller, which increases the contact with the solvent, and is more conducive to the refining and purification of organic solvents such as acetone or ethanol and pure water, so that the purification of polyetheretherketone can be more thorough and the residual diphenyl sulfone can be greatly reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 3 is a scanning electron microscope image of the polyetheretherketone powder prepared in Example 1 of the present invention.
[0021] Figure 2 3 is a scanning electron microscope image of the polyetheretherketone powder prepared in Example 2 of the present invention.
[0022] Figure 3 It is a scanning electron microscope image of the polyetheretherketone powder prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0023] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0024] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0025] Embodiment 1, S1. Preparation of hydroxyapatite / diphenyl sulfone composite materials 400 g of diphenyl sulfone was placed in 800 mL of acetone, and the temperature was raised to 60 °C until the diphenyl sulfone was dissolved. Then, 12.5 g of hydroxyapatite with a mass content of 10 wt% (as a percentage of polyetheretherketone) was added to the diphenyl sulfone liquid, ultrasonicated for 1 hour, heated to 80 °C, and mechanically stirred until the acetone was completely volatilized to obtain hydroxyapatite / diphenyl sulfone composite powder.
[0026] S2, 400 g of hydroxyapatite / diphenyl sulfone composite powder were added to the reactor, the pressure was reduced and vacuumed, an inert gas was introduced to normal pressure, and a condenser reflux device was connected under the protection of the inert gas; the temperature was raised to 180 °C while heating and stirring, and after the diphenyl sulfone was melted, 42.40 g of sodium carbonate, 87.26 g of difluorobenzophenone and 48.45 g of hydroquinone were added, and the temperature was gradually raised to 320 °C. After reacting for 2.5 h, when the target molecular weight was reached, the reaction product was cooled and the powder was taken out.
[0027] S3. Heat 400 g of diphenyl sulfone to 290 °C, add the above-mentioned polymerization product, and cool the dissolved polyetheretherketone solution to 250 °C; the cooling rate is 5 °C / min; when the sample temperature is lower than 250 °C, cool it naturally, and crush the sample by a crusher (particle size is 60-80 mesh). The crushed sample is washed five times with acetone and pure water respectively, filtered, and vacuum dried at a temperature of 150 °C for 6 h.
[0028] Embodiment 2, S1. Preparation of titanium dioxide / diphenyl sulfone composite materials The hydroxyapatite was replaced by titanium dioxide, and the rest was the same as S1 in Example 1.
[0029] S2 and 400 g of titanium dioxide / diphenyl sulfone composite powder were added to the reaction kettle, and the rest was the same as S2 in Example 1.
[0030] S3, heat 800 g of diphenyl sulfone to 290°C, add the above-mentioned polymerization product, and the rest is the same as S3 in Example 1.
[0031] Embodiment 3, S1. Preparation of graphene oxide / diphenyl sulfone composite materials The hydroxyapatite was replaced by graphene oxide, and the rest was the same as S1 in Example 1.
[0032] S2 and 400 g of graphene oxide / diphenyl sulfone composite powder were added to the reaction kettle, and the rest was the same as S2 in Example 1.
[0033] S3. Directly heat the above-mentioned polymer product to 290° C. The rest is the same as S3 in Example 1.
[0034] Embodiment 4, S1. Preparation of silica / diphenyl sulfone composite materials The hydroxyapatite was replaced by silicon dioxide, and the rest was the same as S1 in Example 1.
[0035] S2: 400 g of silicon dioxide / diphenyl sulfone composite powder was added to the reaction kettle, and the rest was the same as S2 in Example 1.
[0036] S3: 400 g of diphenyl sulfone was heated to 290° C., the above-mentioned powder reactant was added, and the dissolved polyetheretherketone solution was cooled to 260° C.; the rest was the same as S3 in Example 1.
[0037] Embodiment 5: S1. Preparation of silica / diphenyl sulfone composite materials The hydroxyapatite was replaced by silicon dioxide, and the rest was the same as S1 in Example 1.
[0038] S2: 400 g of silicon dioxide / diphenyl sulfone composite powder was added to the reaction kettle, and the rest was the same as S2 in Example 1.
[0039] S3: 400 g of diphenyl sulfone was heated to 290° C., the above-mentioned powder reactant was added, and the dissolved polyetheretherketone solution was cooled to 255° C.; the rest was the same as S3 in Example 1.
[0040] Embodiment 6, S1, same as S1 in Example 1 S2. Same as S2 in Example 1.
[0041] S3, heat 400 g of diphenyl sulfone to 290°C, add the above-mentioned polymerization product, and cool the dissolved polyetheretherketone solution to 250°C; the cooling rate is 20°C / min; the rest is the same as S3 in Example 1.
[0042] Embodiment 7, S1, same as S1 in Example 1 S2. Same as S2 in Example 1.
[0043] S3, heat 400 g of diphenyl sulfone to 290°C, add the above-mentioned polymerization product, and cool the dissolved polyetheretherketone solution to 250°C; the cooling rate is 10°C / min; the rest is the same as S3 in Example 1.
[0044] Embodiment 8, S1. Same as S1 in Example 1.
[0045] S2. Same as S2 in Example 1.
[0046] S3, heat 400 g of diphenyl sulfone to 290°C, add the above-mentioned polymerization product, and cool the dissolved polyetheretherketone solution to 250°C; the cooling rate is 3°C / min; the rest is the same as S3 in Example 1.
[0047] Embodiment 9, S1. Add 5.8 g of hydroxyapatite with a mass content of 5 wt% into the diphenyl sulfone liquid. The rest is the same as S1 in Example 1.
[0048] S2 and 400 g of hydroxyapatite / diphenyl sulfone composite powder were added into the reaction kettle, which was the same as S2 in Example 1.
[0049] S3. Same as S3 in Example 1.
[0050] Embodiment 10 S1. Add 29 g of hydroxyapatite with a mass content of 20 wt% into the diphenyl sulfone liquid, as in S1 in Example 1. As in S1 in Example 1.
[0051] S2 and 400 g of hydroxyapatite / diphenyl sulfone composite powder were added into the reaction kettle, which was the same as S2 in Example 1.
[0052] S3. Same as S3 in Example 1.
[0053] Comparative Example 1 S1. Same as S1 in Example 1.
[0054] S2. Same as S2 in Example 1.
[0055] S3, heat 400 g of diphenyl sulfone to 290° C., add the above-mentioned polymerization product, and directly cool the dissolved polyetheretherketone solution. The rest is the same as S3 in Example 1.
[0056] Comparative Example 2 S1: 400 g of diphenyl sulfone powder was added to the reactor, and the pressure was reduced and vacuumed. Inert gas was introduced to normal pressure. Under the protection of inert gas, a condenser reflux was connected; the temperature was raised to 180 °C while heating and stirring. After the diphenyl sulfone was melted, 42.40 g of sodium carbonate, 87.26 g of difluorobenzophenone and 48.45 g of hydroquinone were added, and the temperature was gradually raised to 320 °C. After reacting for 2.5 hours, when the target molecular weight was reached, the reaction product was cooled and the powder was taken out. The sample was crushed by a pulverizer, and the crushed sample was washed five times with acetone and pure water respectively, filtered, and vacuum dried at a temperature of 150 °C for 6 hours.
[0057] S2: 10 g of hydroxyapatite with a mass content of 10 wt% and 90 g of polyetheretherketone powder were put into a high-speed mixer and mixed for 30 min to obtain a polyetheretherketone composite material.
[0058] Test results: Figure 1 and Figure 2The scanning electron microscope image of the bioactive material modified polyetheretherketone powder prepared in Examples 1 and 2, the scale in the figure is 50 μm. It can be seen from the figure that the particle size of the modified polyetheretherketone powder prepared by the present invention is less than 30 μm, and the surface morphology of the powder is relatively complete. This is because the solvent selected by the present invention can completely dissolve the polyetheretherketone polymerization product, so that the polyetheretherketone resin molecular chain rearranges and crystallizes into tiny particles, and the concentration of PEEK in the system is adjusted. When the PEEK concentration is low, induced crystallization occurs under the solvent effect to form particles with smaller particle size. The amount of solvent used is relatively small, and the polyetheretherketone cannot be completely dissolved, and the prepared modified PEEK powders adhere to each other.
[0059] Figure 3 This is a scanning electron microscope image of the modified polyetheretherketone powder prepared in Comparative Example 1. The system in Comparative Example 1 did not undergo a slow cooling process, but was directly cooled to room temperature. When the cooling rate was faster, the crystal growth time became shorter and the average particle size of the prepared modified PEEK powder became larger.
[0060] Table 1 Average particle size of modified PEEK powder obtained in Examples and Comparative Examples
[0061] The data of metal particle content in the purified sample after microwave digestion is shown in Table 2. It can be seen that the content of metal particles in the PEEK composite powder prepared by the method of the present invention is lower and more in line with the use requirements of medical grade PEEK.
[0062] Table 2 PEEK composite powder metal particle content data
[0063] According to the national standard GB / T14233.2-2005 (GB / T 16886.5-2003), the ultrafine powder in Example 1 was subjected to a cytotoxicity test by an in vitro cytotoxicity test extract test (MTT method). The cell morphology was normal, and the cytotoxicity test results were shown in Table 3. As can be seen from the table, the bioactive material modified polyetheretherketone material prepared by the present invention has good biological activity, which broadens the application of PEEK materials in the preparation of biomedical implant materials.
[0064] Table 3 Cytotoxicity of ultrafine powder in Example 1
[0065] Table 4 shows the mechanical properties of the bioactive material modified polyetheretherketone materials prepared in Example 1 of the present invention and Comparative Example 2. It can be seen from the data in Table 4 that in the PEEK composite powder prepared by the method of the present invention, the mixing between PEEK and the nanomaterial is more uniform, and the mechanical properties of the PEEK composite material are more excellent.
[0066] Table 4 Mechanical properties of PEEK composite powder
Claims
1. A method for preparing a medical-grade bioactive material / PEEK composite powder, comprising the following steps: S1, dispersing the bioactive material in the dissolved diphenyl sulfone, and heating until the solvent evaporates to obtain a bioactive material / diphenyl sulfone composite material; S2, adding the bioactive material / diphenyl sulfone composite material into a reaction kettle, heating under an inert atmosphere until the diphenyl sulfone is melted, adding sodium carbonate, difluorobenzophenone and hydroquinone, and continuing heating to react; S3, heating the polymer product of step S2, and then cooling it to 250-260°C; when the temperature drops to 250°C, cooling it naturally, crushing the obtained sample with a crusher, and washing it with acetone and water or ethanol and water respectively.
2. The preparation method according to claim 1, characterized in that: In step S1, the bioactive material is a medical filler; The amount of the bioactive material added is not higher than 35% of the mass of the PEEK resin.
3. The preparation method according to claim 1 or 2, characterized in that: In step S1, acetone, ethanol or ether is used to dissolve the diphenyl sulfone; After the diphenyl sulfone is dispersed, ultrasound is performed and the mixture is heated to 60-80° C. until the solvent is completely volatilized.
4. The preparation method according to any one of claims 1 to 3, characterized in that: In step S2, the temperature is raised to 150-180° C. to melt the diphenyl sulfone.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In step S2, the temperature is continued to rise to 300-320°C for reaction for 2-3 hours.
6. The preparation method according to any one of claims 1 to 5, characterized in that: In step S3, the diphenyl sulfone is heated to 290-300° C., the polymerization product is added, and then the temperature is lowered.
7. The preparation method according to any one of claims 1 to 6, characterized in that: In step S3, the cooling rate is 5-20°C / min.
8. The preparation method according to any one of claims 1 to 7, characterized in that: In step S3, after washing, suction filtration and vacuum drying are performed, and the vacuum drying temperature is 100-150° C. and the time is 4-8 h.
9. Medical-grade bioactive material / PEEK composite powder prepared by the method according to any one of claims 1 to 8.